Alginate-Chitosan hydrogels containing shRNA plasmid for inhibition of CTNNB1 expression in breast cancer cells - (:unkn) unknown (My University, 2023)
The hydrogels prepared with alginate and chitosan polymers were prepared to deliver the shRNA-encoding plasmid (pshRNA) to MDA-MB-231 cells for the inhibition of β-catenin (CTNNB1), which was reported to be overexpressed in breast cancer. Polyion complex hydrogels prepared using sodium alginate and chitosan were characterized by Fourier transform infrared spectrometry (FTIR) analysis, scanning electron microscope (SEM) analysis, swelling, and degradation properties. After the release properties and serum stability of pshRNA-loaded hydrogels were determined, their cytotoxicity, transfection efficacy, and effects on CTNNB1 expression were investigated in MDA-MB-231 cells. All hydrogels were shown to protect pshRNA from the enzymatic activity of serum and to deliver pshRNA to cells efficiently. As a result of transfection studies, pshRNA-loaded hydrogels reduced CTNNB1 expression by up to 30.25%. Cell viability also decreased by 38% in cells treated with 2.5% (w/v) alginate-chitosan hydrogel containing pshRNA targeting CTNNB1. Alginate-chitosan hydrogels were shown to be a suitable matrix system for local gene delivery.
Keywords: Biyomedikal Mühendisliği; Kimya; Biyokimya; Biyoinorganik Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Biomedical Engineering; Chemistry; Biochemistry; Bioinorganic Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Malzeme Bilimi; MALZEME BİLİMİ, BİYOMATERYAL; POLİMER BİLİMİ; KİMYA, ORGANİK; MÜHENDİSLİK, BİYOMEDİKAL; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; MATERIALS SCIENCE; CHEMISTRY; MATERIALS SCIENCE, BIOMATERIALS; POLYMER SCIENCE; CHEMISTRY, ORGANIC; ENGINEERING, BIOMEDICAL; Biyomühendislik; Fizik Bilimleri; Biyomalzemeler; Organik Kimya; Polimerler ve Plastikler; Bioengineering; Physical Sciences; Biomaterials; Organic Chemistry; Polymers and Plastics; breast cancer; chitosan; hydrogel; shRNA; sodium alginate; sodium alginate; chitosan; breast cancer; shRNA; hydrogel